The Effect of Job Training and Work Environment on Employee Performance Through Job Satisfaction at BPR Alwashliyah: - Roni, Shofyan (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Employee performance is very determining progress something company Because performance is something very important thing in effort organization For reach objective . If employee own good performance _ naturally will give impact profitable for company vice versa _ if performance employee low so company will experience difficulties and losses in achievement goals that have been determined by the Company. Study This aim For test and analyze influence training and environment Work to performance employee through satisfaction Work in a way direct nor in a way No direct . Approach used _ in study This is approach causal . Population in study This is all over BPR Alwashliyah employees . Deep sample study This use sample fed up totaling 50 people from BPR Alwashliyah . Deep data collection techniques study This use technique documentation , observation , and questionnaires . Deep data analysis techniques study This use approach quantitative use analysis statistics with using the Analysis test Outer Model , Inner Model Analysis , and Hypothesis Testing . Deep data processing study This using the PLS ( Partial Least Square ) software program . Research result This show that in a way direct training , environment work and satisfaction Work influential significant to performance employees , training and environment Work influential significant to satisfaction Work as well as in a way No direct training and environment Work influential significant to performance employee through satisfaction works at BPR Alwashliyah